Microwave hybrid process-based fabrication of super duplex stainless steel joints using nickel and stainless steel filler materials - Singh Parminder; Prajapati Deoraj; Sehgal Shankar (High Temperature Materials and Processes)
This study introduces a joining procedure applicable to super duplex stainless steel (SAF2507) alloys through the microwave hybrid heating (MHH)-based process using nickel (Ni) and stainless steel (SS304) filler powders. Mechanical test results of the Ni-filler joints revealed an average value of microhardness of 432 HV and an ultimate tensile strength value of 442 MPa. Similarly, SS304 filler joints showed an average value of microhardness of 461 HV and an ultimate tensile strength of 534 MPa. The hardness of SS304 filler joints was 6.71% more than that of Ni-filler joints. Increased hardness leads to better ear properties, which are required in many engineering applications. Furthermore, the tensile strength of SS304 filler joints was 20.81% better than that of Ni-filler joints. Better tensile strength of joints is a major requirement from a design safety point of view. Energy-dispersive spectroscopy results revealed the presence of iron, chromium, molybdenum, nickel, manganese, and carbon elements in the weld zone. Furthermore, the microstructural analysis performed using scanning electron microscopy showed a robust metallurgical bonding among the two interface surfaces, leading to the formation of good quality joints with no interfacial cracking.